Utilization of Slags from Foundry Process - Pribulová, Alena; Futáš, Peter; Bartošová, Marianna; Petrík, Jozef (Journal of Casting & Materials Engineering, 2018)
The melting of steel or cast iron is one step of the foundry process. The foundry industry uses different types of furnaces, and metallurgical slags are products of the pyrometallurgical processes defecting in these furnaces. Furnace slag is a non-metallic by-product that consists primarily of silicates, alumina silicates, and calcium-alumina-silicates. As a by-product of the melting process, furnace slags vary considerably in form depending on the melted metal furnace types, and slag cooling method used. Most quantity of slags from the foundry processes are created in a cupola furnace that is used for cast iron production. An electric arc furnace is usually used for steel production, but it can be used for cast iron production as well. Universal use features an electric induction furnace. Slags from the melting processes in a foundry can be in the form of gravel, or the slag from a cupola furnace can be granulated. The utilization of slags from foundry processes is very delimited in Slovakia because of their quantity. This article deals with the possibility of using foundry slag as a binder in civil engineering. A basic property of a binder in civil engineering is its hydraulicity, which can be given by compression strength. Four metallurgical slags were tested. The values of the compressive strength of the slags were low, but addition cement to the slags resulted in a strong increase in the value of the compressive strength.